2014
DOI: 10.1590/1678-4499.0277
|View full text |Cite
|
Sign up to set email alerts
|

Outbreaks of Chrysodeixis includens (Walker) (Lepidoptera: Noctuidae) in common bean and castor bean in São Paulo State, Brazil

Abstract: Since 2009, increasing populations of Chrysodeixis includens (Walker) (Lepidoptera: Noctuidae) have been observed in cultivated common bean (Phaseolus vulgaris L.) and castor bean (Ricinus communis L.) at the Lageado Experimental Farm, belonging to the FCA/UNESP, Botucatu, São Paulo State, Brazil. Defoliations around 80% and 50% were observed in the common bean cv. Pérola and castor bean cv. IAC-2028, respectively. Samples of individuals (caterpillars and pupae) were collected in the field, and kept in laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 5 publications
0
20
0
3
Order By: Relevance
“…Specht et al (2016) assessed the reproduction potential of S. eridania in soybean and noticed that the number of copulated females was not affected by the size of pupae; however, differences were observed while analyzing egg fertility and adult longevity. Souza et al (2014) studied ten soybean cultivars and found that the duration and survival rate of the larval stage, the duration of the pupal stage, cycle duration, and larval weight were the main biological variables that contributed to the evaluation of the antibiosis effect on S. eridania. In the present study, the same evaluated variables also played an important role in determining the effect of soybean antibiosis on C. includens.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Specht et al (2016) assessed the reproduction potential of S. eridania in soybean and noticed that the number of copulated females was not affected by the size of pupae; however, differences were observed while analyzing egg fertility and adult longevity. Souza et al (2014) studied ten soybean cultivars and found that the duration and survival rate of the larval stage, the duration of the pupal stage, cycle duration, and larval weight were the main biological variables that contributed to the evaluation of the antibiosis effect on S. eridania. In the present study, the same evaluated variables also played an important role in determining the effect of soybean antibiosis on C. includens.…”
Section: Resultsmentioning
confidence: 99%
“…According to Souza et al (2014), the PI 227687 and PI 227682 soybean cultivars expressed high antibiosis effects on S. eridania, and IAC 100 and DM 339 were found to provide moderate resistance, extending the life cycle of this insect. Boiça Júnior et al (2015) also observed that the Dowling cultivar extended the duration of the larval stage of S. cosmioides, which was considered as an indicative of low-quality food.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of chemicals and transgenic plants is a major control measure employed in the management of C. includens [1] [2]. Among the commonly used insecticides, there is an obstacle due to two aspects: resistant, and the lack of knowledge about the lethal and sublethal effects of insecticides on the pest [6] [7].…”
Section: Introductionmentioning
confidence: 99%